Influence of beam reinforcement on exterior beam-column joints - Kumar V. (My University, 2025)
Sixteen specimens simulating typical exterior beam-column joints subjected to axial compression and uniaxial bending were tested. The effects of column axial load, shear and tension reinforcements of the beam on the performance of joints were studied. It was found that the efficiency of joints increases with the increase in axial load on column and with the increase in tensile and shear reinforcements in the beam.